Evaluation of long‐term effects of artificial sweeteners on rat brain: a biochemical, behavioral, and histological study. Issue 6 (16th April 2018) - Erbaş, Oytun; Erdoğan, Mümin Alper; Khalilnezhad, Asghar; Solmaz, Volkan; Gürkan, Fulya Tuzcu; Yiğittürk, Gürkan; Eroglu, Hüseyin Avni; Taskiran, Dilek
Abstract: The aim of the present study was to compare the effects of artificial sweeteners (aspartame, saccharin, and sucralose) on rat brain. Twenty‐four adult male Sprague–Dawley rats were included in the study. The control group ( n  = 6) received regular tap water, whereas other groups received aspartame (3 mg/kg/day, n  = 6, ) or saccharin (3 mg/kg/day, n  = 6) or sucralose (1.5 mg/kg/day, n  = 6) in the drinking water. Following 6 weeks, the passive avoidance learning (PAL) test was performed to evaluate the neurobehavioral effects of sweeteners. The brains were assessed for lipid peroxides, neuron count, and Glial fibrillary acidic protein (GFAP) immunohistochemistry. Our results demonstrated that chronic intake of sweeteners significantly impaired PAL performance in all groups. Hippocampal CA1–CA3 areas revealed significantly lower neuronal count in aspartame and increased GFAP expression in all groups. Brain lipid peroxides were significantly higher in all groups. Our findings suggest that long‐term consumption of artificial sweeteners may have harmful effects on cognition and hippocampal integrity in rats.